Physical and biogeochemical properties in landfast sea ice (Barrow, Alaska): Insights on brine and gas dynamics across seasons. Issue 6 (26th June 2013) - Zhou, Jiayun; Delille, Bruno; Eicken, Hajo; Vancoppenolle, Martin; Brabant, Frédéric; Carnat, Gauthier; Geilfus, Nicolas‐Xavier; Papakyriakou, Tim; Heinesch, Bernard; Tison, Jean‐Louis
Abstract : [1] The impacts of the seasonal evolution of sea‐ice physical properties on ice‐ocean biogeochemical exchanges were investigated in landfast ice at Barrow (Alaska) from January through June 2009. Three stages of brine dynamics across the annual cycle have been identified based on brine salinity, brine volume fraction, and porous medium Rayleigh number (Ra). These are sea‐ice bottom‐layer convection, full‐depth convection, and brine stratification. We further discuss the impact of brine dynamics on biogeochemical compounds in sea ice: stable isotopes of water (δD, δ 18 O), nutrients (NO3 −, PO4 3−, NH4 + ), microalgae (chlorophyll‐a), and inert gas (argon). In general, full‐depth convection events favor exchanges between sea ice and seawater, while brine stratification limits these exchanges. However, argon responds differently to brine dynamics than the other biogeochemical compounds analyzed in this study. This contrast is attributed to the impact of bubble nucleation on inert gas transport compared to the other biogeochemical compounds. We present a scenario for argon bubble formation and evolution in sea ice and suggest that a brine volume fraction approaching 7.5–10% is required for inert gas bubbles to escape from sea ice to the atmosphere. Key Points: The stages of the brine dynamics within sea ice over the full growth‐decay cycle Link between brine dynamics and ice‐ocean exchanges of biogeochemical compounds First scenario for inert gas entrapment and migration in sea ice